Multi-material Design in the Case of a Coupled Selection of Architectures and Materials: Application to Embedded Electronic Packaging - Baracchini, Paul; Guillebaud, Claire; Kromm, François-Xavier; Wargnier, Hervé (Journal of materials engineering and performance, 2019)
The objective of this study was to produce a methodology for designing multi-materials. This methodology was to be applied to an electronic embedded packaging structure for the aeronautics field. The reference material used for the electronic packaging was substituted for a multi-material able to combine the benefits of both material and architecture in order to enhance performance. The design of the multi-material was based on a coupled selection of materials and architectures performed using materials and geometrical pattern databases. The methodology provided both the optimal design in response to specifications and a large diversity of optimized designs (in terms of architectures and materials) relevant for the conceptual design stage. First, the optimal design of the electronic packaging was determined using a genetic algorithm. Next, the built approach integrated a hybridization of the genetic algorithm with a backtracking algorithm in order to propose optimized designs in a controlled time. Finally, the search space was modified by removing optimal designs previously identified by the genetic algorithm in order to determine a wide diversity of optimized designs.